A method for preparing highly effective antibacterial and antiviral functional fiber
By using nitrogen-doped carbon quantum dot-loaded nano-copper in PA6 fibers, the problem of PA6 fiber lacking antibacterial, antiviral and antiodor functions is solved, and efficient and long-lasting antibacterial, antiviral and deodorizing effects are achieved, suitable for high-quality high-quality high-quality high-quality high-quality high-quality high-quality high-quality high-quality high-quality high-quality high-quality high-quality high-quality high-quality high-quality high-quality high-quality high-quality high-quality high-quality high-quality high-quality high-quality high-quality high-quality high-quality high-quality high-quality high-quality high-quality high-quality high-quality high-quality high-quality high-quality high-quality high-quality high-quality high-quality high-quality high-quality high-quality high-quality high-quality high-quality high-quality high-quality high-quality high-quality high-quality high-quality high-quality high-quality high-quality high-quality high-quality high-quality high-quality Required application areas.
Patent Information
- Application Number
- CN202310353462.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-04
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2043-04-04
AI Technical Summary
The existing PA6 fiber lacks antibacterial, antiviral and antiodor functions, and the existing nanoCu element is easily oxidized, making it difficult to meet the efficient and long-lasting antibacterial, antiviral and deodorizing needs.
A one-step hydrothermal method is used to prepare nitrogen-doped carbon quantum dots (N-CQDs), nanocopper is generated by in-situ reduction on its surface, carboxylic acid modification is carried out, and composite spinning is combined with polyamide 6 fibers to form a leather core structure. antibacterial and antiviral PA6 composite fiber.
It achieves efficient and long-lasting antibacterial and antiviral effects, and effectively eliminates smoke odor under no light conditions, improving the application field and performance of fibers.
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of antibacterial and antiviral fiber synthesis, and relates to a method for preparing antibacterial and antiviral polyamide 6 fiber, and in particular to a method for preparing highly efficient and durable antibacterial, antiviral and smoke odor eliminating polyamide 6 composite fiber by nitrogen-doped carbon quantum dots loaded with nano-copper. Background Art
[0002] Polyamide 6 (PA6) has the characteristics of good wear resistance, self-lubrication and oil resistance, and has been widely used in civil yarns, industrial yarns, engineering plastics, etc. As people's living standards have significantly improved, the requirements for quality of life are getting higher and higher. PA6 fiber itself does not have antibacterial and antiviral capabilities. In addition to paying attention to its practicality, people pay more attention to the antibacterial, antiviral and anti-odor properties of the fiber. If PA6 fiber is given antibacterial, antiviral and anti-odor capabilities, it can not only broaden the application market of PA6 fiber, but also meet people's demand for antibacterial, antiviral and deodorizing fibers.
[0003] The antibacterial modification of PA6 fiber is generally achieved by adding antibacterial agents. According to the chemical composition, antibacterial agents can be divided into three categories: natural antibacterial agents, organic antibacterial agents, and inorganic antibacterial agents. Both natural antibacterial agents and organic antibacterial agents have the disadvantages of being heat-resistant and not durable, and organic antibacterial agents are also toxic and easily absorbed by the human body. Inorganic antibacterial agents have strong antibacterial ability and good effects, and are widely used in the market. Inorganic antibacterial agents include two categories: metal ion antibacterial agents and photocatalytic antibacterial agents. Metal ion antibacterial agents use ion overflow to disinfect microorganisms such as bacteria and viruses, but they only inhibit the reproduction of bacteria on the surface and inside of the material. At the same time, they can also cause harm to the human body, and some metal ions are more active, and redox reactions will occur in the air, causing fiber discoloration. Photocatalytic antibacterial agents produce reactive oxygen free radicals (ROS), which can act in bacterial and viral cells, thereby killing bacteria and viruses.
[0004] Nano Cu is a non-ionic overflow antibacterial agent. When applied to PA6 fiber, it can solve the problem of metal ion overflow and endanger human health. Nano Cu kills bacteria and viruses by converting oxygen into ROS, and can play an antibacterial and antiviral role without specific conditions. However, nano Cu is easily oxidized, and copper and nitrogen-doped carbon quantum dots are both nano-scale materials and are prone to agglomeration. In addition, the nicotine smell produced by cigarette burning in life is easily adsorbed on the surface of fiber fabrics, affecting the wearing experience of the fabrics. Existing technologies cannot meet people's urgent needs for antibacterial, antiviral, and anti-odor composite functional fibers and fabrics. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a fiber with both antibacterial and antiviral functions and anti-odor functions. The present invention adopts the following technical scheme: a method for preparing an antibacterial, antiviral and smoke-odor-eliminating PA6 fiber by loading nano-copper on N-CQDs with a C=N or C=O structure, using a one-step hydrothermal method to prepare N-CQDs, and then using an in-situ reduction method to generate nano-element copper (Cu@N-CQDs) with a size of 2-10nm on the surface of N-CQDs, and then using carboxylic acid to modify Cu@N-CQDs to obtain carboxylic acid-modified Cu@N-CQDs (CM-Cu@N-CQDs), in-situ introducing Cu@N-CQDs during the synthesis of polyamide 6 to obtain antibacterial and antiviral polyamide 6, and finally using antibacterial and antiviral PA6 as the skin layer and conventional PA6 as the core layer through composite spinning to obtain an antibacterial and antiviral PA6 composite fiber.
[0006] The nitrogen-doped carbon quantum dots N-CQDs used in the present invention are 3-5 nm in size and are a new type of fluorescent carbon nanoparticles with excellent biocompatibility, good dispersibility and low preparation cost, and have important application value in the fields of optical imaging and photocatalysis. The present invention first discovered that N-CQDs with C=N or C=O structure will not only generate ROS (hydroxyl radicals, superoxide radicals and singlet oxygen) to kill bacteria and viruses under photocatalytic conditions, but also the electron-pushing groups C=N or C=O on the surface of N-CQDs can also undergo π-π conjugation effect with the electron-pushing group C=N on the surface of nicotine to generate fluorescence resonance energy transfer. When fluorescence resonance energy is transferred, in the new energy transfer system constructed by N-CQDs (energy donor) and nicotine (energy acceptor), fluorescence energy is transferred from N-CQDs (donor) to nicotine (acceptor), that is, the fluorescence of N-CQDs (donor) is quenched and the fluorescence of nicotine (acceptor) is enhanced. After fluorescence quenching, N-CQDs use more energy to degrade nicotine, achieving the effect of eliminating smoke odor. Combining it with nano copper can produce a composite functional fiber with higher performance and wider application of antibacterial, antiviral and deodorizing properties.
[0007] The nano copper element obtained by the present invention has a size of 2-10nm, and has extremely high catalytic antibacterial and antiviral activity. The nano copper element can activate oxygen in water and air to generate reactive oxygen radicals (ROS). ROS has extremely strong oxidizing properties and can directly or indirectly damage the structure and function of cells and kill bacteria and viruses. The in-situ reduction method generates nano copper element (Cu@N-CQDs) with a size of 2-10nm on the surface of N-CQDs, and then the Cu@N-CQDs are modified with carboxylic acid. The CM-Cu@N-CQDs obtained by carboxylic acid modification not only have good compatibility with PA6, but also can be evenly and stably dispersed in the PA6 melt in the in-situ polymerization of polyamide monomers, solving the problem of uneven dispersion of Cu@N-CQDs. And the carboxyl group can be well complexed with nano copper, so the nano copper of Cu@N-CQDs can be kept in a reduced state all the time, and ROS can be continuously released to achieve a long-term antibacterial and antiviral effect. In addition, nano-copper exerts antibacterial and antiviral effects under light-free conditions, which solves the defect that N-CQDs need sunlight excitation to exert antibacterial and antiviral effects. The two synergistically have antibacterial, antiviral and deodorizing effects, further expanding the application field of antibacterial, antiviral and deodorizing fibers.
[0008] The present invention adopts a skin-core structure for spinning, the high-efficiency antibacterial and antiviral PA6 component of the skin layer plays an antibacterial and antiviral role, and the conventional PA6 component of the core layer plays a role in supporting mechanical properties. Therefore, the fiber obtained by the present invention not only has a healthy, efficient and long-lasting antibacterial and antiviral effect, but also can eliminate smoke odor, and can be used in application fields with high requirements for fiber strength, antibacterial and antiviral, and deodorization composite functional properties.
[0009] The present invention provides a method for preparing a highly effective antibacterial and antiviral functional fiber, and the specific steps are as follows:
[0010] (1) By weight, 2 to 10 parts of o-phenylenediamine are ultrasonically dispersed in 100 parts of 95% ethanol to prepare an o-phenylenediamine solution, and 2 to 10 parts of acid are ultrasonically dispersed in 100 parts of 95% ethanol to prepare an acid solution, the o-phenylenediamine solution and the acid solution are mixed and added into a stainless steel autoclave, reacted at 160 to 260° C. for 0.5 to 18 hours to obtain a dark brown solution, the obtained product is washed with deionized water and anhydrous ethanol, centrifuged and separated, and finally dried to obtain nitrogen-doped carbon quantum dots N-CQDs;
[0011] (2) Ultrasonic dispersion of 3 to 5 parts of nano-N-CQDs in 50 parts of deionized water under certain conditions to prepare an N-CQDs aqueous solution, and dissolving 0.6 to 1.2 parts of copper salt in 50 parts of deionized water to prepare a copper ion aqueous solution. The N-CQDs aqueous solution and the copper ion aqueous solution are mixed in a flask, condensed and refluxed, and then 50 parts of the reducing agent aqueous solution are added dropwise to the flask while stirring, and stirred at 60 to 90°C for 3 to 24 hours to obtain a dark solution. The obtained product is separated by centrifugation from deionized water and anhydrous ethanol, and finally dried to obtain a nano-N-CQDs-loaded nano-copper composite antibacterial agent. The size of the generated nano-element copper is 2-10nm;
[0012] (3) 1 to 3 parts of aliphatic dibasic acid, 15 to 20 parts of nano-N-CQDs loaded nano-copper composite antibacterial agent (Cu@N-CQDs) and 0.5 to 2 parts of caprolactam are added to 100 parts of anhydrous ethanol, condensed and refluxed, and stirred for 0.5 to 5 hours to obtain carboxylic acid-modified nano-N-CQDs loaded nano-copper composite antibacterial agent slurry (CM-Cu@N-CQDs slurry), and then the modified CM-Cu@N-CQDs slurry is placed in a centrifuge tube and centrifuged, the supernatant is removed, and the precipitate is washed with ethanol and water for 3 to 5 times, and then dried to obtain carboxylic acid-modified CM-Cu@N-CQDs.
[0013] (4) By weight, 1 to 3 parts of CM-Cu@N-CQDs, 100 parts of caprolactam, and 2 to 5 parts of deionized water are added to a polymerization reactor, firstly ring-opening prepolymerization, then polycondensation, and finally strip casting, pelletizing, and extraction to obtain composite antibacterial and antiviral PA6 slices.
[0014] (5) High-efficiency antibacterial and antiviral PA6 slices and conventional PA6 slices are dried at 90-120° C. for 24-36 hours, and the antibacterial and antiviral PA6 and conventional PA6 are added into a composite spinning machine in a certain proportion for spinning, with the antibacterial and antiviral PA6 as the skin layer and the conventional PA6 as the core layer, to obtain high-efficiency antibacterial and antiviral PA6 composite fibers.
[0015] In the method for preparing a highly effective antibacterial and antiviral functional fiber as described above, in step (1), the conditions for ultrasonic dispersion of o-phenylenediamine and acid are that the time is 20 to 60 minutes and the ultrasonic frequency is 30 to 60 kHz;
[0016] In the method for preparing a highly effective antibacterial and antiviral functional fiber as described above, in step (1), the acid is one of benzenesulfonic acid, folic acid, boric acid, acetic acid, terephthalic acid, and tartaric acid;
[0017] In the method for preparing a highly effective antibacterial and antiviral functional fiber as described above, in step (2), the certain conditions for ultrasonic dispersion of N-CQDs under certain conditions refer to a time of 20 to 60 minutes and an ultrasonic frequency of 30 to 60 kHz;
[0018] In the method for preparing a highly effective antibacterial and antiviral functional fiber as described above, in step (2), the copper salt refers to one of copper chloride, copper sulfate, and copper nitrate;
[0019] In the method for preparing a highly effective antibacterial and antiviral functional fiber as described above, in step (2), the reducing agent aqueous solution refers to a 0.1-0.5 mol / L aqueous solution of citric acid, hydrazine hydrate, sodium borohydride, ascorbic acid, sodium hypophosphite, or tetrabutylammonium borohydride;
[0020] In the method for preparing a highly effective antibacterial and antiviral functional fiber as described above, in step (3), the aliphatic dibasic acid is one of adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, and dodecanedioic acid;
[0021] In the method for preparing a high-efficiency antibacterial and antiviral functional fiber as described above, in step (4), the reaction conditions of the ring-opening prepolymerization are a temperature of 200 to 260° C., a pressure of 0.1 to 1.0 MPa, and a time of 2 to 5 h;
[0022] In the method for preparing a high-efficiency antibacterial and antiviral functional fiber as described above, in step (4), the polycondensation reaction conditions are a temperature of 240 to 260° C., a pressure of -0.02 to -0.10 MPa, and a time of 2 to 5 hours;
[0023] In the method for preparing a high-efficiency antibacterial and antiviral functional fiber as described above, in step (5), the antibacterial and antiviral polyamide 6 and conventional polyamide are in a certain ratio, which means the mass ratio is (1-3):2.
[0024] According to the method for preparing a high-efficiency antibacterial and antiviral functional fiber as described above, in step (5), the antibacterial and antiviral polyamide 6 composite fiber has a breaking strength of 2.5-4.0 cN / dtex, a breaking elongation of 15-30%, and an antibacterial and antiviral effect on Staphylococcus aureus, Escherichia coli, Candida albicans, and influenza virus A (H1N1) of more than 99%. The photocatalytic degradation effect of the antibacterial and antiviral fiber on nicotine under simulated sunlight was determined by ultra-high performance liquid chromatography (UPLC), and it was found that after 75 minutes of sunlight irradiation, the degradation effect of the antibacterial and antiviral fiber on nicotine can reach more than 99%. After the fiber was washed 50 times, the antibacterial and antiviral effect on Staphylococcus aureus, Escherichia coli, Candida albicans, and influenza virus A (H1N1) was still more than 97%, and the degradation effect on nicotine was more than 97%. The high-efficiency and long-lasting antibacterial and antiviral fiber of the present invention has good water washing resistance, high-efficiency antibacterial and antiviral properties, and good smoke odor elimination performance.
[0025] Beneficial effects of the present invention:
[0026] (1) Safety: The present invention is a non-dissolving antibacterial and antiviral additive, which will not cause harm to the human body and the environment, and is healthier and safer;
[0027] (2) Long-lasting antibacterial properties: The nano-copper of the present invention is always in a reduced state and continuously releases ROS, which significantly improves the durability of antibacterial and antiviral properties;
[0028] (3) Highly efficient antibacterial: The nano-Cu and N-CQDs in the present invention work synergistically and can play an antibacterial and antiviral role without any specific conditions, thus achieving highly efficient antibacterial and antiviral functions and having excellent smoke odor elimination functions;
[0029] (4) Spinnability: The antibacterial and antiviral PA6 composite fiber of the present invention has good spinnability and high mechanical properties. DETAILED DESCRIPTION
[0030] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0031] Example 1, a method for preparing a highly effective antibacterial and antiviral functional fiber, the specific steps are as follows:
[0032] (1) By weight, 1.5 parts of o-phenylenediamine were ultrasonically dispersed in 100 parts of 95% ethanol to prepare an o-phenylenediamine solution, 3 parts of acid were ultrasonically dispersed in 100 parts of 95% ethanol to prepare an acid solution, the o-phenylenediamine solution and the acid solution were mixed in a polytetrafluoroethylene liner, the polytetrafluoroethylene liner was placed in a 100 mL stainless steel autoclave, and hydroheated at 160° C. for 12 h to obtain a dark brown solution, the obtained product was washed with deionized water and anhydrous ethanol, centrifuged, and finally dried to obtain N-CQDs;
[0033] (2) 3 parts of N-CQDs were ultrasonically dispersed in 50 parts of deionized water at a frequency of 60kHz for 20 minutes to prepare an N-CQDs aqueous solution, and 0.6 parts of anhydrous copper sulfate were dissolved in 50 parts of deionized water to prepare a copper ion aqueous solution. The N-CQDs aqueous solution and the copper ion aqueous solution were mixed in a flask and condensed and refluxed at 80°C, and then 50 parts of 0.1 mol / L citric acid aqueous solution were added dropwise to the flask while stirring, and stirred at 60°C for 3 hours to obtain a dark solution. The obtained product was centrifuged from deionized water and anhydrous ethanol, and finally dried to obtain an N-CQDs-loaded nano-copper composite antibacterial agent (Cu@N-CQDs).
[0034] (3) 1.5 parts of adipic acid, 15.5 parts of Cu@N-CQDs and 1.5 parts of caprolactam were added to 100 parts of anhydrous ethanol, condensed and refluxed at 80°C, and stirred for 0.5 h to obtain carboxylic acid-modified N-CQDs loaded with nano-copper composite antibacterial agent slurry (CM-Cu@N-CQDs slurry). The CM-Cu@N-CQDs slurry was then placed in a centrifuge tube and centrifuged. The supernatant was removed and the precipitate was washed three times with ethanol and water, and then dried to obtain carboxylic acid-modified Cu@N-CQDs (CM-Cu@N-CQDs).
[0035] (4) 1.5 parts of CM-Cu@N-CQDs, 100 parts of caprolactam, and 2.5 parts of deionized water were added to a polymerization reactor, firstly carried out a ring-opening prepolymerization at 200°C and 0.1 MPa for 2 h, and then carried out a condensation polymerization at 240°C and -0.02 MPa for 2 h. Finally, high-efficiency antibacterial and antiviral poly-PA6 chips were obtained through strip casting, pelletizing, and extraction.
[0036] (5) The high-efficiency antibacterial and antiviral PA6 slices and the conventional PA6 slices were dried at 110°C for 36 hours, and the antibacterial and antiviral PA6 was used as the skin layer and the conventional PA6 was used as the core layer. The antibacterial and antiviral PA6 and the conventional polyamide were added into a composite spinning machine at a mass ratio of 1:2 for spinning to obtain a high-efficiency antibacterial and antiviral PA6 composite fiber.
[0037] The high-efficiency antiviral PA6 fiber prepared by the present invention has a breaking strength of 4.5 cN / dtex and a breaking elongation of 30%. The antibacterial and antiviral effects on Staphylococcus aureus, Escherichia coli, Candida albicans and influenza virus A (H1N1) are 99.1%, and the degradation effect on nicotine is 99.2%. After the fiber is washed 50 times, the antibacterial and antiviral effects on Staphylococcus aureus, Escherichia coli, Candida albicans and influenza virus A (H1N1) are still more than 97%, and the degradation effect on nicotine is more than 97.1%. The fiber has good water-washing resistance, high-efficiency antibacterial and antiviral properties, and good smoke odor elimination performance.
[0038] Example 2, a method for preparing a highly effective antibacterial and antiviral functional fiber, the specific steps are as follows:
[0039] (1) By weight, 4 parts of o-phenylenediamine were ultrasonically dispersed in 100 parts of 95% ethanol to prepare an o-phenylenediamine solution, 6 parts of acid were ultrasonically dispersed in 100 parts of 95% ethanol to prepare an acid solution, the o-phenylenediamine solution and the acid solution were mixed in a polytetrafluoroethylene liner, the polytetrafluoroethylene liner was placed in a 100 mL stainless steel autoclave, and hydrothermal was performed at 220° C. for 10 h to obtain a dark brown solution, the obtained product was washed with deionized water and anhydrous ethanol, centrifuged, and finally dried to obtain N-CQDs;
[0040] (2) 5 parts of N-CQDs were ultrasonically dispersed in 50 parts of deionized water at a frequency of 30kHz for 60 minutes to prepare an N-CQDs aqueous solution, and 1 part of copper chloride was dissolved in 50 parts of deionized water to prepare a copper ion aqueous solution. The N-CQDs aqueous solution and the copper ion aqueous solution were mixed in a flask and condensed and refluxed at 80°C, and then 50 parts of 0.5 mol / L ascorbic acid aqueous solution were added dropwise to the flask while stirring, and stirred at 90°C for 24 hours to obtain a dark solution. The obtained product was centrifuged from deionized water and anhydrous ethanol, and finally dried to obtain an N-CQDs-loaded nano-copper composite antibacterial agent (Cu@N-CQDs).
[0041] (3) Add 2.5 parts of suberic acid, 16 parts of TiO2-Cu and 1 part of caprolactam to 100 parts of anhydrous ethanol, condense and reflux at 80°C, and stir for 5 hours to obtain carboxylic acid-modified N-CQDs loaded with nano-copper composite antibacterial agent slurry (CM-Cu@N-CQDs slurry). Then, put the CM-Cu@N-CQDs slurry into a centrifuge tube and centrifuge it. After removing the supernatant, the precipitate obtained is washed with ethanol and water 5 times, and then dried to obtain carboxylic acid-modified Cu@N-CQDs (CM-Cu@N-CQDs).
[0042] (4) 1 part of CM-Cu@N-CQDs, 100 parts of caprolactam, and 3 parts of deionized water were added to a polymerization reactor, firstly carried out a ring-opening prepolymerization at 260°C and 1.0 MPa for 5 h, then a condensation reaction was carried out at 260°C and -0.10 MPa for 5 h, and finally, a highly efficient antibacterial and antiviral PA6 slice was obtained through strip casting, pelletizing, and extraction.
[0043] (5) The high-efficiency antibacterial and antiviral PA6 slices and the conventional PA6 slices were dried at 110°C for 28 hours, and the antibacterial and antiviral PA6 was used as the skin layer and the conventional PA6 was used as the core layer. The antibacterial and antiviral PA6 and the conventional polyamide were added into a composite spinning machine at a mass ratio of 3:2 for spinning to obtain a high-efficiency antibacterial and antiviral PA6 composite fiber.
[0044] The high-efficiency antiviral PA6 fiber prepared by the present invention has a breaking strength of 3.0 cN / dtex and a breaking elongation of 27%. The antibacterial and antiviral effects on Staphylococcus aureus, Escherichia coli, Candida albicans and influenza virus A (H1N1) are 99.9%, and the degradation effect on nicotine is more than 99.8%. After the fiber is washed 50 times, the antibacterial and antiviral effects on Staphylococcus aureus, Escherichia coli, Candida albicans and influenza virus A (H1N1) are still more than 97%, and the degradation effect on nicotine is more than 97.4%. The fiber has good water washing resistance, high-efficiency antibacterial and antiviral properties, and good smoke odor elimination performance.
[0045] Example 3, a method for preparing a highly effective antibacterial and antiviral functional fiber, the specific steps are as follows:
[0046] (1) By weight, 6 parts of o-phenylenediamine were ultrasonically dispersed in 100 parts of 95% ethanol to prepare an o-phenylenediamine solution, 7.5 parts of acid were ultrasonically dispersed in 100 parts of 95% ethanol to prepare an acid solution, the o-phenylenediamine solution and the acid solution were mixed in a polytetrafluoroethylene liner, the polytetrafluoroethylene liner was placed in a 100 mL stainless steel autoclave, and hydrothermal was performed at 230° C. for 8 h to obtain a dark brown solution, the obtained product was washed with deionized water and anhydrous ethanol, centrifuged, and finally dried to obtain N-CQDs;
[0047] (2) 3 parts of N-CQDs were ultrasonically dispersed in 50 parts of deionized water at a frequency of 40kHz for 40 minutes to prepare an N-CQDs aqueous solution, and 1.2 parts of copper chloride were dissolved in 50 parts of deionized water to prepare a copper ion aqueous solution. The N-CQDs aqueous solution and the copper ion aqueous solution were mixed in a flask and condensed and refluxed at 80°C, and then 50 parts of 0.3 mol / L ascorbic acid aqueous solution were added dropwise to the flask while stirring, and stirred at 70°C for 20 hours to obtain a dark solution. The obtained product was centrifuged by deionized water and anhydrous ethanol, and finally dried to obtain an N-CQDs-loaded nano-copper composite antibacterial agent (Cu@N-CQDs).
[0048] (3) Add 3 parts of dodecanedioic acid, 20 parts of Cu@N-CQDs and 2 parts of caprolactam to 100 parts of anhydrous ethanol, condense and reflux at 80°C, and stir for 2 hours to obtain carboxylic acid-modified nano-TiO2-loaded nano-copper composite antibacterial agent slurry (CM-Cu@N-CQDs slurry). Then, put the CM-Cu@N-CQDs slurry into a centrifuge tube and centrifuge it. After removing the supernatant, the precipitate obtained was washed with ethanol and water 5 times, and then dried to obtain carboxylic acid-modified Cu@N-CQDs (CM-Cu@N-CQDs).
[0049] (4) 2.5 parts of CM-Cu@N-CQDs, 100 parts of caprolactam, and 4.5 parts of deionized water were added to a polymerization reactor, firstly carried out a ring-opening prepolymerization at 230°C and 0.6 MPa for 4 h, and then carried out a condensation polymerization at 250°C and -0.05 MPa for 4 h. Finally, after strip casting, pelletizing, and extraction, high-efficiency antibacterial and antiviral PA6 slices were obtained.
[0050] (5) The high-efficiency antibacterial and antiviral PA6 slices and the conventional PA6 slices were dried at 120°C for 24 hours, and the antibacterial and antiviral PA6 was used as the skin layer and the conventional PA6 was used as the core layer. The antibacterial and antiviral PA6 and the conventional polyamide were added into a composite spinning machine at a mass ratio of 1:1 for spinning to obtain a high-efficiency antibacterial and antiviral PA6 composite fiber.
[0051] The high-efficiency antiviral polyamide 6 fiber prepared by the present invention has a breaking strength of 4.0 cN / dtex and a breaking elongation of 15%. The antibacterial and antiviral effects on Staphylococcus aureus, Escherichia coli, Candida albicans and influenza A (H1N1) virus reach 99.5%, and the degradation effect on nicotine reaches more than 99.4%. After the fiber is washed 50 times, the antibacterial and antiviral effects on Staphylococcus aureus, Escherichia coli, Candida albicans and influenza A (H1N1) virus still reach more than 97%, and the degradation effect on nicotine reaches more than 97.2%. The fiber has good water washing resistance, high-efficiency antibacterial and antiviral properties and good smoke odor elimination performance.
[0052] Example 4, a method for preparing a highly effective antibacterial and antiviral functional fiber, the specific steps are as follows:
[0053] (1) By weight, 5 parts of o-phenylenediamine were ultrasonically dispersed in 100 parts of 95% ethanol to prepare an o-phenylenediamine solution, 10 parts of acid were ultrasonically dispersed in 100 parts of 95% ethanol to prepare an acid solution, the o-phenylenediamine solution and the acid solution were mixed in a polytetrafluoroethylene liner, the polytetrafluoroethylene liner was placed in a 100 mL stainless steel autoclave, and hydrothermal was performed at 240° C. for 10 h to obtain a dark brown solution, the obtained product was washed with deionized water and anhydrous ethanol, centrifuged, and finally dried to obtain N-CQDs;
[0054] (2) 4.5 parts of N-CQDs were ultrasonically dispersed in 50 parts of deionized water at a frequency of 30kHz for 50 minutes to prepare an N-CQDs aqueous solution, and 1 part of copper chloride was dissolved in 50 parts of deionized water to prepare a copper ion aqueous solution. The N-CQDs aqueous solution and the copper ion aqueous solution were mixed in a flask and condensed and refluxed at 80°C, and then 50 parts of 0.4 mol / L ascorbic acid aqueous solution were added dropwise to the flask while stirring, and stirred at 80°C for 20 hours to obtain a dark solution. The obtained product was centrifuged from deionized water and anhydrous ethanol, and finally dried to obtain an N-CQDs-loaded nano-copper composite antibacterial agent (Cu@N-CQDs).
[0055] (3) Add 2 parts of sebacic acid, 19 parts of Cu@N-CQDs and 1.2 parts of caprolactam to 100 parts of anhydrous ethanol, condense and reflux at 80°C, and stir for 3 hours to obtain carboxylic acid-modified nano-TiO2-loaded nano-copper composite antibacterial agent slurry (CM-Cu@N-CQDs slurry). Then, put the CM-Cu@N-CQDs slurry into a centrifuge tube and centrifuge it. After removing the supernatant, the precipitate obtained was washed with ethanol and water 5 times, and then dried to obtain carboxylic acid-modified Cu@N-CQDs (CM-Cu@N-CQDs).
[0056] (4) 2 parts of CM-Cu@N-CQDs, 100 parts of caprolactam, and 5 parts of deionized water were added to a polymerization reactor, firstly carried out a ring-opening prepolymerization at 250°C and 0.5 MPa for 4 h, then carried out a condensation polymerization at 240°C and -0.06 MPa for 3 h, and finally, after strip casting, pelletizing, and extraction, a highly efficient antibacterial and antiviral polyamide 6 slice was obtained.
[0057] (5) High-efficiency antibacterial and antiviral polyamide 6 slices and conventional polyamide 6 slices were dried at 95°C for 34 hours, and the antibacterial and antiviral polyamide 6 was used as the skin layer and the conventional polyamide 6 was used as the core layer. The antibacterial and antiviral polyamide 6 and the conventional polyamide were added into a composite spinning machine at a mass ratio of 1:2 for spinning to obtain high-efficiency antibacterial and antiviral polyamide 6 composite fibers.
[0058] The high-efficiency antiviral polyamide 6 fiber prepared by the present invention has a breaking strength of 3.5 cN / dtex and a breaking elongation of 18%. The antibacterial and antiviral effects on Staphylococcus aureus, Escherichia coli, Candida albicans and influenza A (H1N1) virus reach 99.9%, and the degradation effect on nicotine reaches more than 99.7%. After the fiber is washed 50 times, the antibacterial and antiviral effects on Staphylococcus aureus, Escherichia coli, Candida albicans and influenza A (H1N1) virus still reach more than 97%, and the degradation effect on nicotine reaches more than 97.3%. The fiber has good water washing resistance, high-efficiency antibacterial and antiviral properties and good smoke odor elimination performance.
[0059] Example 5, a method for preparing a highly effective antibacterial and antiviral functional fiber, the specific steps are as follows:
[0060] (1) By weight, 10 parts of o-phenylenediamine were ultrasonically dispersed in 100 parts of 95% ethanol to prepare an o-phenylenediamine solution, 8.5 parts of acid were ultrasonically dispersed in 100 parts of 95% ethanol to prepare an acid solution, the o-phenylenediamine solution and the acid solution were mixed in a polytetrafluoroethylene liner, the polytetrafluoroethylene liner was placed in a 100 mL stainless steel autoclave, and hydrothermal was performed at 260° C. for 6.5 h to obtain a dark brown solution, the obtained product was washed with deionized water and anhydrous ethanol, centrifuged, and finally dried to obtain N-CQDs;
[0061] (2) 5 parts of N-CQDs were ultrasonically dispersed in 50 parts of deionized water at a frequency of 50kHz for 30 minutes to prepare an N-CQDs aqueous solution, and 0.6 parts of copper chloride were dissolved in 50 parts of deionized water to prepare a copper ion aqueous solution. The N-CQDs aqueous solution and the copper ion aqueous solution were mixed in a flask and condensed and refluxed at 80°C, and then 50 parts of 0.3 mol / L ascorbic acid aqueous solution were added dropwise to the flask while stirring, and stirred at 80°C for 22 hours to obtain a dark solution. The obtained product was separated by centrifugation from deionized water and anhydrous ethanol, and finally dried to obtain a nano-TiO2-loaded nano-copper composite antibacterial agent (Cu@N-CQDs).
[0062] (3) Add 1 part of sebacic acid, 18 parts of Cu@N-CQDs and 0.5 parts of caprolactam to 100 parts of anhydrous ethanol, condense and reflux at 80°C, and stir for 3 hours to obtain carboxylic acid-modified nano-TiO2-loaded nano-copper composite antibacterial agent slurry (CM-Cu@N-CQDs slurry). Then, put the CM-Cu@N-CQDs slurry into a centrifuge tube and centrifuge it. After removing the supernatant, the precipitate obtained was washed with ethanol and water 5 times, and then dried to obtain carboxylic acid-modified Cu@N-CQDs (CM-Cu@N-CQDs).
[0063] (4) 2.5 parts of CM-Cu@N-CQDs, 100 parts of caprolactam, and 3.5 parts of deionized water were added to a polymerization reactor, firstly carried out ring-opening prepolymerization at 240°C and 0.8 MPa for 5 h, then carried out condensation polymerization at 250°C and -0.09 MPa for 2 h, and finally, high-efficiency antibacterial and antiviral PA6 slices were obtained through strip casting, pelletizing, and extraction.
[0064] (5) The high-efficiency antibacterial and antiviral PA6 slices and the conventional PA6 slices were dried at 105°C for 26 hours, and the antibacterial and antiviral PA6 was used as the skin layer and the conventional PA6 was used as the core layer. The antibacterial and antiviral PA6 and the conventional polyamide were added into a composite spinning machine at a mass ratio of 1:1 for spinning to obtain a high-efficiency antibacterial and antiviral PA6 composite fiber.
[0065] The high-efficiency antiviral PA6 fiber prepared by the present invention has a breaking strength of 4.5 cN / dtex and a breaking elongation of 18%. The antibacterial and antiviral effects on Staphylococcus aureus, Escherichia coli, Candida albicans and influenza A (H1N1) virus reach 99.2%, and the degradation effect on nicotine reaches more than 99.3%. After the fiber is washed 50 times, the antibacterial and antiviral effects on Staphylococcus aureus, Escherichia coli, Candida albicans and influenza A (H1N1) virus still reach more than 97%, and the degradation effect on nicotine reaches more than 97.4%. The fiber has good water washing resistance, high-efficiency antibacterial and antiviral properties and good smoke odor elimination performance.
Claims
1. A method for preparing highly effective antibacterial and antiviral functional fibers, characterized in that: The method comprises the following steps: (1) By weight, 2 to 10 parts of o-phenylenediamine are ultrasonically dispersed in 100 parts of 95% ethanol to prepare an o-phenylenediamine solution, 2 to 10 parts of acid are ultrasonically dispersed in 100 parts of 95% ethanol to prepare an acid solution, the o-phenylenediamine solution and the acid solution are mixed and added into a stainless steel autoclave, reacted at 160 to 260° C. for 0.5 to 18 hours to obtain a dark brown solution, the obtained product is washed with deionized water and anhydrous ethanol, centrifuged and separated, and finally dried to obtain nitrogen-doped carbon quantum dots N-CQDs; wherein the conditions for ultrasonic dispersion of o-phenylenediamine and acid refer to a time of 20 to 60 minutes and an ultrasonic frequency of 30 to 60 kHz; the acid refers to one of benzenesulfonic acid, folic acid, boric acid, acetic acid, terephthalic acid, and tartaric acid; (2) 3-5 parts of nano-N-CQDs were ultrasonically dispersed in 50 parts of deionized water under certain conditions to prepare an N-CQDs aqueous solution, and 0.6-1.2 parts of copper salt were dissolved in 50 parts of deionized water to prepare a copper ion aqueous solution; the N-CQDs aqueous solution and the copper ion aqueous solution were mixed in a flask and condensed and refluxed, and then 50 parts of a reducing agent aqueous solution were added dropwise to the flask while stirring, and stirred at 60-90°C for 3-24 hours to obtain a dark solution; the obtained product was separated by centrifugation from deionized water and anhydrous ethanol, and finally dried to obtain a nano-N-CQDs-loaded nano-copper composite antibacterial agent; the size of the generated nano-element copper was 2-10nm; (3) 1-3 parts of aliphatic dibasic acid, 15-20 parts of nano-N-CQDs loaded nano-copper composite antibacterial agent Cu@N-CQDs and 0.5-2 parts of caprolactam are added to 100 parts of anhydrous ethanol, condensed and refluxed, and stirred for 0.5-5 hours to obtain carboxylic acid-modified nano-N-CQDs loaded nano-copper composite antibacterial agent slurry, namely CM-Cu@N-CQDs slurry, and then the CM-Cu@N-CQDs slurry is placed in a centrifuge tube and centrifuged, the supernatant is removed, and the precipitate is washed with ethanol and water for 3-5 times, and then dried to obtain CM-Cu@N-CQDs; (4) By weight, 1-3 parts of CM-Cu@N-CQDs, 100 parts of caprolactam, and 2-5 parts of deionized water were added to a polymerization reactor, firstly ring-opening prepolymerization, then polycondensation, and finally strip casting, pelletizing, and extraction to obtain highly efficient antibacterial and antiviral PA6 slices; (5) High-efficiency antibacterial and antiviral PA6 slices and conventional PA6 slices are dried at 90-120°C for 24-36 hours, and the antibacterial and antiviral PA6 and conventional PA6 are added into a composite spinning machine in a certain proportion for spinning, with the antibacterial and antiviral PA6 as the skin layer and the conventional PA6 as the core layer, to obtain high-efficiency antibacterial and antiviral PA6 composite fibers.
2. The method for preparing a highly effective antibacterial and antiviral functional fiber according to claim 1, characterized in that: In step (2), the certain conditions for ultrasonic dispersion of N-CQDs under certain conditions refer to a time of 20 to 60 minutes and an ultrasonic frequency of 30 to 60 kHz; the copper salt refers to one of copper chloride, copper sulfate, and copper nitrate; and the reducing agent aqueous solution refers to one of a 0.1 to 0.5 mol / L aqueous solution of citric acid, hydrazine hydrate, sodium borohydride, ascorbic acid, sodium hypophosphite, and tetrabutylammonium borohydride.
3. The method for preparing a highly effective antibacterial and antiviral functional fiber according to claim 1, characterized in that: In step (3), the aliphatic dibasic acid refers to one of adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, and dodecanedioic acid.
4. The method for preparing a highly effective antibacterial and antiviral functional fiber according to claim 1, characterized in that: In step (4), the reaction conditions for the ring-opening prepolymerization are a temperature of 200-260°C, a pressure of 0.1-1.0 MPa, and a time of 2-5 h; the reaction conditions for the polycondensation are a temperature of 240-260°C, a pressure of -0.02-0.10 MPa, and a time of 2-5 h.
5. The method for preparing a highly effective antibacterial and antiviral functional fiber according to claim 1, characterized in that: In step (5), the antibacterial and antiviral PA6 and conventional PA6 are in a certain ratio, which means the mass ratio is (1-3):
2.
6. The method for preparing a highly effective antibacterial and antiviral functional fiber according to claim 1, characterized in that: The breaking strength of the antibacterial and antiviral polyamide 6 composite fiber is 2.5~4.0cN / dtex, and the elongation at break is 15~30%. The antibacterial and antiviral effect on Staphylococcus aureus, Escherichia coli, Candida albicans, and influenza A (H1N1) virus is more than 99%; the photocatalytic degradation effect of the antibacterial and antiviral fiber on nicotine under simulated sunlight was determined by ultra-high performance liquid chromatography UPLC. After 75 minutes of sunlight irradiation, the degradation effect of the antibacterial and antiviral fiber on nicotine can reach more than 99%; after the fiber was washed 50 times, the antibacterial and antiviral effect on Staphylococcus aureus, Escherichia coli, Candida albicans, and influenza A (H1N1) virus was still more than 97%, and the degradation effect on nicotine reached more than 97%.
Citation Information
Patent Citations
Application of copper-doped carbon dots in antibacterial product
CN112998030A
Preparation method of efficient antibacterial and antiviral fiber
CN114875521A